Exclusion from spheroid formation identifies loss of essential cell-cell adhesion molecules in colon cancer cells - Stadler, Mira (Sci Rep, 2018)
Many cell lines derived from solid cancers can form spheroids, which recapitulate tumor cell clusters and are more representative of the in vivo situation than 2D cultures. During spheroid formation, a small proportion of a variety of different colon cancer cell lines did not integrate into the sphere and lost cell-cell adhesion properties. An enrichment protocol was developed to augment the proportion of these cells to 100% purity. The basis for the separation of spheroids from non-spheroid forming (NSF) cells is simple gravity-sedimentation. This protocol gives rise to sub-populations of colon cancer cells with stable loss of cell-cell adhesion. SW620 cells lacked E-cadherin, DLD-1 cells lost α-catenin and HCT116 cells lacked P-cadherin in the NSF state. Knockdown of these molecules in the corresponding spheroid-forming cells demonstrated that loss of the respective proteins were indeed responsible for the NSF phenotypes. Loss of the spheroid forming phenotype was associated with increased migration and invasion properties in all cell lines tested. Hence, we identified critical molecules involved in spheroid formation in different cancer cell lines. We present here a simple, powerful and broadly applicable method to generate new sublines of tumor cell lines to study loss of cell-cell adhesion in cancer progression.